How Do Critical Thinking Ability and Critical Thinking Disposition Relate to the Mental Health of University Students? - Liu, Zhiyuan; Li, Shuangshuang; Shang, Shouwei; Ren, Xuezhu (Frontiers in Psychology, 2021)
Theories of critical thinking and psychotherapy suggest that human mental problems may be associated with deficiencies in critical thinking. However, empirical evidence is scarce regarding the relationship between critical thinking and mental health and no study has provided an account for the hypothesized relationship between critical thinking and mental health. Our study filled this gap by exploring whether and how critical thinking ability and disposition associate with individual differences in mental health in considering impulsivity which has been revealed to be closely related to both critical thinking and mental health. Results based on a large number of university students indicated that critical thinking skill and disposition explained unique variance of mental health after controlling for impulsivity. Furthermore, the relationship between critical thinking disposition and mental health was mediated by motor and non-planning impulsivity. These findings empirically support the theory of cognitive behavioral therapy, and provide a preliminary account of how human critical thinking associate with mental health. Practically, developing mental health promotion programs for university students is suggested to pay special attention to cultivating their critical thinking (especially critical thinking dispositions).